PENGETAHUAN, PRAKTIK PENCEGAHAN DAN KONDISI RUMAH PADA KONTAK SERUMAH DENGAN PENDERITA TB PARU DI KABUPATEN DEMAK - Didi Setiyadi; M Sakundarno Adi (Dian Nuswantoro Semarang, 2019)
Tuberculosis (TB) is a highly contagious disease. Home contact is an individualwho is susceptible to contracting TB. The purpose of this study was to find outthe knowledge, prevention practices and condition of the house in a householdcontact with tuberculosis patients in Demak Regency.This type of research is observational with a cross sectional design. Thepopulation in the study were all family members of TB patients in July toDecember 2015 who were recorded in three health centers which had the top 3TB cases in Demak District Service. The number of samples is 34 which is one ofthe family members of TB patients who were selected in a simple random. Datawere analyzed using descriptive analysis.The results showed that household contacts with knowledge of good categoriesamounted to 64.7% and respondents with less knowledge categories were35.3%. Household contacts with a good prevention practice category of 52.9%and household contact with the prevention category is less than 47.1%.Household contacts with a healthy home category was 64.7% while householdcontact with unhealthy house category was 35.3%.Keywords: Tuberculosis, knowledge, prevention practices, condition home,house contact, demak